Empire in Lusaka: hip-hop, young men and masculinity in an African city - Mulolani, Happy (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2019)
This study examines young Zambian men who are aspiring hip hop artists in Lusaka and the meanings they make of the representations of masculinity in Empire, a popular US television drama. Broadcast locally via satellite on the South African cable network, DStv, Empire narrates the story of a family of powerful men as they battle for the control of Empire, a successful hip-hop label. Of significance is how the programme's representations of masculinity resonate with the young men's own ideas of masculinity within a highly patriarchal and conservative urban African space. The young male hip-hop artists encounter their everyday experiences in a context of a range of socio-economic challenges within the urban space of Lusaka which presents them with very limited economic opportunities and resources. Underpinned by a constructivist approach, this reception study explores how these young male artists encounter their everyday experiences in the city and how its structural constraints are navigated through hip-hop, a highly popular local cultural form. The male artists' reactions to the programme are dependent on their socio-economic location and the types of skills and resources they draw on in order to traverse their everyday experience of city life which concurrently is perceived as exclusionary and as impacting on their livelihoods and aspirations.
Keywords: Empire (Television program : 2015) -- Influence; Hip-hop -- Zambia -- Lusaka; Young men -- Zambia -- Lusaka; Young men -- Psychology -- Zambia -- Lusaka; Young men -- Social conditions -- Zambia -- Lusaka; Rap musicians -- Zambia -- Lusaka; Masculinity -- Zambia -- Lusaka